2007
DOI: 10.1007/s10812-007-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Passive Q-switching of erbium glass laser by magnesium aluminosilicate sitall with cobalt ions

Abstract: We have studied the radiation output parameters for an erbium glass laser, lasing at a wavelength of 1.54 µm, with passive Q-switching by means of a cobalt-containing magnesium aluminosilicate sitall compared with a saturable absorber based on a magnesium aluminum spinel crystal with cobalt ions. We have shown that the output characteristics of the laser emission when using sitall are not inferior to the analogous characteristics of a laser based on a spinel crystal, and are practically independent of the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…It reached 19% of the free generation pulse energy [242]. A comparison of operation under identical conditions of PS based on Co 2+ :MgAl 2 O 4 crystal and Co 2+ :MAS sitall showed that the materials had similar emission radiation characteristics when used in an Er laser (energy and duration of a single pulse, scatter of these parameters with long-term operation of the laser and over a broad temperature range, M 2 -factor) [243]. TC Co 2+ ions in ZnSe and ZnS crystals are also know as PS for Er lasers.…”
Section: Ermentioning
confidence: 94%
See 1 more Smart Citation
“…It reached 19% of the free generation pulse energy [242]. A comparison of operation under identical conditions of PS based on Co 2+ :MgAl 2 O 4 crystal and Co 2+ :MAS sitall showed that the materials had similar emission radiation characteristics when used in an Er laser (energy and duration of a single pulse, scatter of these parameters with long-term operation of the laser and over a broad temperature range, M 2 -factor) [243]. TC Co 2+ ions in ZnSe and ZnS crystals are also know as PS for Er lasers.…”
Section: Ermentioning
confidence: 94%
“…However, Co 2+ ions in them exhibit anisotropic nonlinear absorption Al 5 O 12 crystals, must be placed appropriately in the laser cavity[232]. Sitalls with crystalline spinel phases and Co 2+ ions incorporated in them can also be used for gain modulation of Er lasers in the spectral region 1.5 μm[121,123,235,[241][242][243]. Emission pulses of duration 100 nsec and energy 7 mJ in a glass Er laser with lamp pumping were recorded using sitalls with Co 2+ :ZnAl 2 O 4 (Co…”
mentioning
confidence: 99%
“…Transition-metal (TM) ion doped glass-ceramics have attracted much interest in recent years, due to their broad range of potential applications, such as photonic devices, ultra-broadband luminescence, and saturable absorbers [2][3][4][5]. In the past decade, transparent GCs with tetrahedral Co 2+ ions containing nanocrystals have been used successfully as passive Q-switchers for 1.3 μm and 1.54 μm lasers [6,7]. They even have better Q-switch performances than Co 2+ -doped crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Co 2+ -doped GCs are prepared by sol-gel technique [4,11,12] or conventional method [6][7][8][9][10]. The advantages of the sol-gel method, as compared with conventional one, are mainly preparation of hybrid materials and low temperature processing [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The GCs are more cost efficient than their single-crystal counterparts because of their faster fabrication process and possibility of mass production. During the past few years, transparent GCs with tetrahedral Co 2+ ions containing nanocrystals have been used successfully as passive Q-switchers for Er:glass laser [3,8,9]. They even have better Qswitch performances than Co 2+ -doped crystals [3].…”
Section: Introductionmentioning
confidence: 99%